Do Insights Influence the Creation of Effective Advertising Campaigns? - Martín Soladana, Irene; Sebastián Morillas, Ana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This study investigates the relationship between the use of insghts and effectiveness in advertising campaigns. To do so, a review of the terms insight and effectiveness is carried out and subsequently, a qualitative methodology is used with a study of 152 cases recognised with a gold medal in the Effectiveness Awards between 2010 and 20221. The results show that working a campaign with an insight can help to achieve effectiveness, but it has been observed that they are not essential to achieve a memorable campaign that meets the business objectives.